Diagnosing Bilirubin Disease in Infants Using the Certainty Factor Method - Br Sitepu, Dinda Isabella; Saragih, Rusmin; Ramadani, Suci (International Journal of Informatics, Economics, Management and Science; Vol 3 No 1 (2024): IJIEMS (January 2024)DO - 10.52362/ijiems.v3i1.1224, 2024)
Poor health and an unhealthy lifestyle are vulnerable to making a person more at risk of experiencing certain health problems or diseases. Bilirubin which is related to health is a metabolite in the form of a yellow pigment derived from the breakdown of heme in hemoglobin. Increased Bilirubin in newborns is a common problem that causes a normal or physiological transition during pregnancy. Al Fuadi General Hospital (RSU Al Fuadi) is a hospital located in Binjai that serves general public health. However, the large number of queues of patients waiting for examination results in a lengthy consultation process and treatment that will be received by Bilirubin sufferers. Based on the existing problems, an expert system is needed that can store information from an expert who can help the hospital. The Certainty Factor method is a method that can prove whether a fact is certain or uncertain in the form of metrics that are usually used in expert systems. Based on the results of trials conducted on this system it can be seen that the level belief from results diagnosis to disease i.e. 93% diagnosed with High Bilirubin disease.